KESEJAHTERAAN PSIKOLOGIS SANTRI DALAM PERSPEKTIF BUDAYA DAN INDIGENOUS PSYCHOLOGY - Ulil Abshar (IAI Sunan Giri Trenggalek, 2025)
This study examines the psychological well-being of students in Islamic boarding schools through the perspective of cultural and indigenous psychology. A literature review was conducted using national and international academic sources. The findings show that the well-being of students is influenced by religiosity, daily spiritual practices, communal relationships, discipline, and guidance from the kyai. The Western-based Psychological Well-being (PWB) model is not entirely suitable for the pesantren context, which emphasizes collective spirituality, hierarchical relationships, and obedience as a process of self-regulation. Therefore, culturally adapted concepts and measurement tools are needed. Practically, pesantren can enhance meaning-making and self-awareness through muhasabah, tadabbur, emotional regulation training, and Islamic mindfulness practices such as sabar, syukur, tawakal, and tazkiyatun nafs to support holistic well-being and spiritual depth